Consumers and Goodwill: Study of Decision Number 297/Pdt. Sus/BPSK/2021 - Denriska Melinda; Kelik Wardiono (Universitas Muhammadiyah Surakarta, 2023)
The Civil Code includes the notion of objective and subjective, contextual and substantial good faith. Article 1338 paragraph (1), which is often known as the Facta Sunt Servanda concept, defines good faith as having an objective meaning or based on the agreement of the parties. The research method used is a legal research method with a doctrinal approach, which is normative in nature. Secondary data in the form of a copy of Court Decision Number 297/Pdt. Sus/BPSK/2021 PN.Plg regarding disputes between business actors over the previous BPSK decision through arbitration settlement due to objections to paying compensation to consumers. In this study used qualitative analysis and deductive reasoning. Legal consideration by the judge in Decision Number 297/Pdt.Sus‐BPSK/2021/PN Plg is in accordance with Law No.30/1999, Law No.8 of 1999, PERMA 01/2006, BPSK Decision No.57/BPSK/PTS /XII/2021 to reject all applications because none of the a quo fulfills the material requirements for the objection referred to in Article 6 paragraph 3 and 4 PERMA 01/2006 while against that between the objection applicant and the respondent in making an agreement already fulfills the elements of article 1338 in full objective and heeding the norms of decency and decency, then the applicant is willing to fulfill and pay compensation to the respondent because the applicant is deemed to have defaulted in carrying out the agreement.